Prevalence of fungal infection among Iranian patients with chronic sinusitis - NAGHIBZADEH, B. (Pacini Editore SpA, 2011)
Chronic sinusitis is a major cause of morbidity today. Regional variations in the incidence of this disease have been reported. The aim of this study was to evaluate the incidence of fungal infection as the causative agent of chronic sinusitis among Iranian patients. A cross sectional hospital based study was designed; the patients underwent paranasal sinus washing and maxillary sinus biopsy. All specimens were studied by light microscopy. Fungal culturing was employed to confirm diagnosis. The patients underwent Computed Tomography for sinus evaluation. Of 162 participants, 12 samples from patients showed fungal elements, 2 of them Aspergillus fulvous (1.2%), 9 of them Alternaria species (5.56%) and 1 of them Psilomysis (0.6%). All patients presented radiologic evidence of sinusitis, ranging from mucosal thickening to total opacity. In conclusion, results obtained showed a low prevalence of fungal sinusitis among Iranian patients with chronic sinusitis. Findings also showed that Alternaria is the most causative agent.